1907 Minn. Gen. Laws 408-09 - (:unkn) unknown (My University, 1907)
An Act to Prohibit the Shooting of Firearms Within Three Miles of the Corporate Limits of Cities Having a Population of 50,000 or More, ch. 300, § 1: unlawful for any person to hunt with or carry loaded any rifle or other firearm for the purpose of hunting within three miles of the corporate limits of any city having a population of 50,000 or more, except target practice on regular rifle ranges, and members of duly organized gun clubs shooting or practicing on lands owned or leased by the club, or trap shooter shooting or practicing on grounds selected for that purpose, or firing a salute over the graves of soldiers.§
Keywords: HUNTING REGULATION